CULPRIT ARTERY CHARACTERISTICS AND SEVERITY OF ANGIOGRAPHIC THROMBUS BURDEN IN PRIMARY PERCUTANEOUS CORONARY INTERVENTION IN PATIENTS PRESENTING WITH ST ELEVATION MYOCARDIAL INFARCTION - Siddiqui, Abdul Hameed; Aziz, Sohail; Khan, Qaiser; Sharif, Hamid; Majeed, Syed Mohammad Imran; Irfan, Muhammad; Khan, Muhammad Nadir; Samore, Naseer Ahmed; Abbas, Shahid (Pakistan Armed Forces Medical Journal, 2022)
Objective: The purpose of study was to characterize culprit artery characteristics in terms of presence of thrombus burden in patients with acute myocardial infarction using prevalent parameters of thrombus estimation.Study design: Descriptive study.Place and Duration of Study: Adult cardiology departments of Armed Forces Institute of Cardiology / National Institute of Heart Diseases (AFIC/NIHD) from 1st October 2011 to 31st September 2012.Patients and Methods: We studied 119 patients treated with primary percutaneous coronary intervention for STsegment myocardial infarction. Bare metal stents were used in all patients as per hospital protocol. Thrombus burden (TB) was graded (G) as G0 = no thrombus, G1= possible thrombus, G2 = small [greatest dimension < ½ vessel diameter (VD)], G3 = moderate (>1/2 but 2 VD), G5 = unable to assess TB due to vessel occlusion. Patients with G5 were reassessed after passage of guide wire or small balloon for thrombus burden.Results: Frequency of major adverse cardiac events (MACE)-defined as death, myocardial infarction and infarctrelated artery revascularization was recorded for the peri-procedural period which was defined in our study up to 72 hours. Overall, in hospital MACE was 8.4%. Conclusion: Large thrombus burden is a significant predictor for mortality and MACE.